Hubungan Daya Ledak Otot Tungkai Dengan Kecepatan Tendangan Sabit Pencak Silat PSHt Rayon Jaya Bakti Ranting Tuah Negeri Cabang Musi Rawas - Nurwati Desnawa Rahayu Aji (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2021)
This study aims to determine the relationship between limb muscle explosive power and sickle kick speed in pencak silat participants at PSHT Rayon Jaya Bakti Ranting Tuah Negeri Musi Rawas Branch with quantitative research and a correlation method. With a population of 34 silat participants and a sample of 30 silat participants, the sampling technique was purposive sampling. Leg muscle explosive power instrument using verticaljump, and the speed of the sickle kick by kicking towards the sandsack. Data analysis to test hypotheses requires prerequisite tests that must be met so that the results can be justified. The analysis prerequisite test includes the normality test and linearity test. The analysis as for the test results and data with the title of the relationship between limb muscle explosive power and sickle kick speed in pencak silat participants PSHT Rayon Jaya Bakti Ranting Tuah Negeri Musi Rawas Branch, data processing using SPSS 21 can be seen that belonging to the 0.40-0.59 category, it can be stated that there is a relationship between the explosive power of the leg muscles and the speed of the sickle kick in the pencak silat participants of PSHT Rayon Jaya Bakti Ranting Tuah Negeri Musi Rawas Branch. Keywords: Explosive Power and Sickle Kick Speed